The influence of tailored risk communication on individual adaptive behaviour. (October 2020) - Attems, Marie-Sophie; Thaler, Thomas; Snel, Karin A.W.; Davids, Peter; Hartmann, Thomas; Fuchs, Sven
Abstract: Hydro-meteorological hazards annually lead to considerable economic losses worldwide. Property level flood risk adaptation (PLFRA) measures have shown to decrease potential damages by floods and other hazards. However, such measures are often implemented inadequately, frequently because of lacking communication between public administration and homeowners. Thus, risk communication systems have been created by multiple actors, ranging from the government to private companies and insurance groups, which have the goal to communicate risks to homeowners and businesses in a tailored manner. Consequently, adaptive behaviour can be triggered by risk communication. This paper conducted a cross-comparison of several risk communication systems which encompassed an output in the shape of a label or guideline, based on semi-structured interviews with relevant experts. One system, the German Hochwasserpass, was focused on in more detail. The results show that risk communication systems should include participatory approaches with experts to trigger adaptive behaviour. However, even in an example including mutual knowledge transfer a gap between knowledge about mitigation measures and actually implementing them was present. Thus, this implies going a step beyond, which ultimately questions the resource efficiency of such risk communication systems on a larger scale.